The impact of low to high waste cooking oil-based biodiesel blends on toxic organic pollutant emissions from heavy-duty diesel engines. (November 2019) - Cheruiyot, Nicholas Kiprotich; Hou, Wen-Che; Wang, Lin-Chi; Chen, Chia-Yang
Abstract: As yet, the effect of biodiesels on the emissions of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) from heavy-duty diesel engines (HDDEs) has only been studied using limited fuel blend ratios. To clarify the influence of using higher fractions of biodiesel on the emissions of toxic organic pollutants from diesel engines, in this research, the emissions of PM, PAHs, and persistent organic pollutants (POPs) from EURO IV and EURO III HDDEs fueled by low to high waste cooking oil (WCO)-based biodiesel-petrodiesel fuel blends were studied, including D100 (0% biodiesel), B20 (20%), B40 (40%), B60 (60%), B80 (80%), and B100 (100%). The engines were tested according to the US FTP-75 test procedure. The results for the EURO IV diesel engine showed that the PM and toxic organic pollutant emissions were reduced with increases in the blending ratio up until the B60 scenario when compared to the D100 scenario. This is because biodiesel has higher oxygen content and no or lower aromatic content than petrodiesel. Nevertheless, during the B80 and B100 scenarios, the PM and toxic organic pollutant emissions increased due to the high viscosity property of biodiesel, which negatively affected the combustion process. The biodiesel effect on the emissions from EURO III engine was more pronounced because of its lower combustion efficiency, and therefore the improvement in combustion using biodiesel resulted in greater PCDD/F reductions. Highlights: Using biodiesel improved combustion and resulted in PAH and POP reductions. PAHs and POPs decreasing trend was observed till B60 in the EURO IV engine. Poor combustion due to high viscosity increased PAHs and POPs in B80 and B100. Biodiesel effect on PCDD/F emissions was more pronounced in the EURO III engine. Biodiesel reduce PAHs and POPs from diesel engines with the appropriate blending ratio.